DETERMINATION OF DISCHARGE COEFFICIENT THROUGH LABORATORY TESTING USING BROAD-CRESTED WEIR - Baihaqi, Reza; Herawati, Henny; Soeryamassoeka, S. B. (Fakultas Teknik Universitas Tanjungpura, 2024)
This study examined the impact of different threshold widths and channel narrowing configurations on water flow characteristics. The research involved testing three threshold widths (AL1, AL2, AL3) and six narrowing models (PM10, PM15, PM20, PT10, PT15, PT20) with varying water heights (1.0 cm, 1.5 cm, and 2.0 cm) above the threshold. Results indicated that narrowing at the upstream end increased water levels upstream and downstream, with a corresponding rise in flow velocity at the downstream end. Discharge values and coefficients varied significantly across different configurations, with non-linear increases observed in discharge coefficients due to changes in water levels and velocities. Scaling calculations provided prototype channel dimensions and flow characteristics, highlighting the study's strengths in using a fiberglass open channel and diverse testing configurations. However, limitations include the laboratory scale and exclusion of channel roughness effects.